UTILIZING CARTOON SERIES AS PEDAGOGICAL MEDIA TO ENRICH YOUNG LEARNERS’ VOCABULARY - Tatu Zakiyatun Nufus (JURNAL DARMA AGUNG, 2023)
Cartoon series is one media that can be used in teaching vocabulary for young learners, it consists of the interesting pictures and guessing vocabulary. This present study was conducted to see the utilization of cartoon series in the classroom and find out the effectiveness of cartoon series to enrich young learners’ vocabulary. The method that is used in this research is qualitative. The data collection technique used in this research is observation. The samples of this study are 10 young learners. The researcher uses World word’s cartoon as a media to teach vocabulary to young learners. Then, the researcher analyzes descriptively and summarizes the findings, and provides new ideas by collaborating on all findings at the sources. The finding of the research is using cartoon series in the learning process helps the students to learn new vocabulary and also interested and gain new experiences and knowledge that they can take from these lessons.